2006
DOI: 10.1080/14634980600724023
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metal pollution status in the Malaysian aquatic environment

Abstract: The objective of this paper was to review the status of the Malaysian aquatic environment with respect to heavy metals. Much of the work on metals focused on measurements in biota and sediments, but very little research has been done on dissolved and particulate metals in water, metal speciation in sediments or on the bioavailability of metals. Cadmium (Cd), Copper (Cu), Lead (Pb) and Zinc (Zn) received much attention but due to technical difficulties, Arsenic, (As), Mercury (Hg), Tin (Sn) and other hydride el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
73
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(74 citation statements)
references
References 12 publications
1
73
0
Order By: Relevance
“…Studies on the bioaccumulation of metals are limited. As reported by Shazili et al (2006), the bio-concentration factors (BCF) of 132 -12900 ×103 for Cu, 580-76000 for Pb and 481-17200 for Cr were estimated in rock oysters from Kalong Bay, Kemaman and values of 0.9 × 10-3 -1.9 × 10-3 for Pb, 8.0 × 10-3 for Cu and 2.6 × 10−3 to 3.3 × 10−3 for Cd from Crassostrea belcherici (oyster) cultured at the Merbuk estuary. Another indicator of bioaccumulation property is the biota-sediment accumulation factors (BSAFs) which is the ratio of biota to sediment contamination concentration.…”
Section: Introductionsupporting
confidence: 67%
See 2 more Smart Citations
“…Studies on the bioaccumulation of metals are limited. As reported by Shazili et al (2006), the bio-concentration factors (BCF) of 132 -12900 ×103 for Cu, 580-76000 for Pb and 481-17200 for Cr were estimated in rock oysters from Kalong Bay, Kemaman and values of 0.9 × 10-3 -1.9 × 10-3 for Pb, 8.0 × 10-3 for Cu and 2.6 × 10−3 to 3.3 × 10−3 for Cd from Crassostrea belcherici (oyster) cultured at the Merbuk estuary. Another indicator of bioaccumulation property is the biota-sediment accumulation factors (BSAFs) which is the ratio of biota to sediment contamination concentration.…”
Section: Introductionsupporting
confidence: 67%
“…The abundance of Nerita lineata and Thais bitubercularis along the shores of Peninsular Malaysia and the ability to bioaccumulate heavy metals made them a potential biomonitor organisms for marine pollution [3]. Earlier reports by [1] indicated that the levels of heavy metals in the fish, bivalves and shrimp were within the safe limits of the Malaysian Food Act of 1983. The levels of Pb and Cd were elevated in the Thais sp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, we noticed that the content of Zn in Pacific oyster and marsh clam were exceeding the permissible limits. Studies have shown that oysters have the ability to accumulate many heavy metals [46]. Meanwhile, marsh clam has been reported to capable of accumulating the highest level of heavy metals among 13 species of clams collected from 34 sites on the Malaysian coasts [47].…”
Section: Zincmentioning
confidence: 99%
“…The west coast area is much more developed compared with the east coast area as it is adjacent to the busiest strait in the world, Malacca strait [5,6]. Six study sites have been selected in west coast area, on the basis of the occurrence of the S. cucullata and different site characteristics.…”
Section: Methodsmentioning
confidence: 99%